Transversus abdominis plane block as a sole anesthetic technique for open appendectomy in patient with Treacher Collins syndrome: a case report. Issue 12 (12th December 2020) - Siddiqui, Khalid Maudood; Ali, Muhammad Asghar; Salim, Bushra
Abstract: Patients with Treacher Collins syndrome (TCS) present serious challenges to anesthetist in securing of airway; upper airway obstruction and difficult tracheal intubation are considered complex entity in these patients. This case report describes the significance of transversus abdominis plane (TAP) block as a sole anesthetic choice in appendectomy where airway management can be avoided. A 17-year-old boy, known case of TCS, presented with acute appendicitis underwent emergency laparotomy. Surgery was successfully performed by TAP block with dexmedetomidine infusion. Open appendectomy can be performed successfully in certain circumstances under TAP block with adjunctive use of dexmedetomidine infusion where airway handling is avoided. Further studies are warranted to distinct its use as sole anesthetic choice in lower abdominal surgeries.